2006
DOI: 10.1111/j.1750-3841.2006.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Residual Oxygen on the Storage Life of Retail‐Ready Fresh Beef Steaks Masterpackaged Under a CO2 Atmosphere

Abstract: Retail-packed rump (Gluteus medius, GM) and striploins (Longissiumus dorsi, LD) steaks were masterpackaged under carbon dioxide (CO 2 ) and stored at 1 • C ± 1 • C for 14, 28, 35, and 42 d. A commercial oxygen (O 2 ) scavenger (ATCO HV1000 , Standa Industrie, Caen, France) was used in the masterpacks to achieve an O 2 -free atmosphere. Similar packages without the O 2 scavengers were also prepared. At each storage time, 2 masterpacks of each treatment were opened and the retail trays were placed in a display c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 14 publications
(24 reference statements)
1
20
0
2
Order By: Relevance
“…The use of oxygen scavengers, A and B effectively reduced oxygen concentration during master pack storage (p < 0.05). Similar results by Venturini et al (2006) and Limbo et al (2013) showed that oxygen scavengers rapidly reduced oxygen concentration in master packs during storage and that these concentrations were lower when compared to packages without oxygen scavengers. There were significant interactions of oxygen scavenger with ground beef (p < 0.0001) and oxygen scavenger with storage time for headspace oxygen concentrations (p < 0.0001).…”
Section: Gas Concentrationssupporting
confidence: 72%
See 4 more Smart Citations
“…The use of oxygen scavengers, A and B effectively reduced oxygen concentration during master pack storage (p < 0.05). Similar results by Venturini et al (2006) and Limbo et al (2013) showed that oxygen scavengers rapidly reduced oxygen concentration in master packs during storage and that these concentrations were lower when compared to packages without oxygen scavengers. There were significant interactions of oxygen scavenger with ground beef (p < 0.0001) and oxygen scavenger with storage time for headspace oxygen concentrations (p < 0.0001).…”
Section: Gas Concentrationssupporting
confidence: 72%
“…The presence of ground beef also increased the average oxygen concentration compared to packages without meat (p < 0.05). This increase in oxygen concentration in master packs may be related to entrapped oxygen in the meat, in the overwrap tray headspace or in the tray matrix in cases where polystyrene foam trays are used (Limbo et al, 2013;Tewari et al, 2002;Venturini et al, 2006Venturini et al, , 2014. The use of oxygen scavengers, A and B effectively reduced oxygen concentration during master pack storage (p < 0.05).…”
Section: Gas Concentrationsmentioning
confidence: 97%
See 3 more Smart Citations